Relationships of body habitus and SUV indices with signal-to-noise ratio of hepatic 18F-FDG PET. Issue 5 (May 2016) - Keramida, G.; Dunford, A.; Siddique, M.; Cook, G.J.; Peters, A.M.
Abstract: Objective: Tissue accumulation of 18 F-FDG is quantified as standardised uptake value (SUV), which may be expressed as the voxel maximum (SUVmax ) or mean (SUVmean ). SUVmax /SUVmean may be a marker of hepatic steatosis, while the coefficient of variation (CV) of SUV may be a marker of hepatic fat distribution heterogeneity (HFDH). Alternatively, they may reflect low signal-to-noise ratio ('noise') in obese persons in whom hepatic steatosis is common. The study aim was to compare the impact of body size on noise versus SUV and CT density (CTD). Methods: Dynamic PET was performed (30 × 1 min frames) following FDG injection in 60 patients undergoing routine PET/CT. Hepatic FDG clearance was measured using Patlak-Rutland graphical analysis with abdominal aorta as input. Noise was quantified as the standard deviation (SD) of the plot residuals (ignoring the first 2 frames), normalised to the intercept (NRMSD). SUVmax, SUVmean and CTD were measured from 60 min whole body PET/CT. CV of SUV and SD of CTD were quantified in 28/60 patients using texture analysis. Results: NRMSD correlated with weight (r = 0.49; p < 0.0001) and BMI (r = 0.48; p = 0.0001). SUVmax, SUVmean, SUVmax /SUVmean, CV of SUV, CTD, and SD of CTD all correlated strongly with weight and BMI (p < 0.0001). However, they correlated weakly with NRMSD, the strongest being SUVmax (r = 0.34; p = 0.008) and SD of CTD (r = 0.42; n = 28; p = 0.026). Conclusions: Noise is increased in overweight/obese persons but has little effect on SUV indices, CTD and their variabilities. SUVmax /SUVmean and CV of SUV are therefore, to some extent, markers of hepatic steatosis and HFDH, respectively.